Studying the efficiency of locally isolated Klebsiella pneumoniae and Bacillus cereus In Bioremediation of Petroleum Hydrocarbon - الشاخ علا; تميم عليا; أميمة ناصر (Latakia University Journal -Biological Sciences Series, 2024)
The use of indigenous microorganisms in the bioremediation of hydrocarbon petroleum to cleanup environment has become a valuable technique. In this study two strains of bacteria Klebsiella pneumoniae and Bacillus cerues have been tested to remove engine oil. The results showed that both K. pneumoniae and B.cereus have ability to remove petroleum hydrocarbons in Bushnell Hass Broth medium containing 126mg/l engine oil as sole carbon source, but K . pneumoniae was more efficient in the bioremediation of engine oil than B.cereus.The results obtained showed the K. pneumoniae strain degradation efficacy was 83.17% on 20 day compared to B.cereus 65.291%. furthermore the rate growth of K. pneumoniae strain was faster than that of the B.cerues strain. Spectrum results by Spectrophotometric analysis and colorimetric using DCPIP (2,6 dichlorophanelin- dophenol) revealed that The isolate K. pneumoniae showed 79.79 % of biodegradation on 7day compared to B.cereus 61.23%.